Dense heterointerfaces and unsaturated coordination synergistically accelerate electrocatalysis in Pt/Pt₅P₂ porous nanocages - Li, Yinghao (2022)
Designing cost-effective and durable Pt-based catalysts is vital and challenging for practicable energy storage and conversion technologies. Here, a fast phosphating strategy to establish a Pt/Pt5P2 porous nanocage with numerous heterointerfaces and defects is presented. It exhibits extraordinary activity and stability for both hydrogen evolution reaction (HER) with a small overpotential of 29 mV at 10 mA cm−2 and methanol oxidation reaction (MOR) with a high mass activity of 1.37 A mg−1Pt at peak values, surpassing Pt/C. Microstructural analyzes show that many stacking faults are induced around heterointerfaces, while rich vacancies and atomic steps are created by the phosphorus-induced thermal migration of Pt atoms, serving as highly active low-coordination sites. X-ray absorption spectroscopy and theoretical calculations reveal that introducing P atoms can modify the electronic configuration of Pt, thus optimizing H2O/H* binding strength and lowering water dissociation energy to accelerate HER, while decreasing the energy barrier of the rate-limiting step (*CHO to *HCOOH) to facilitate MOR.